Potential of conservation agriculture for ecosystem services: A review - GHOSH, SONAKA; DAS, T K; SHARMA, D K; GUPTA, KAMLIKA (The Indian Journal of Agricultural Sciences, 2019)
Conservation agriculture (CA) has emerged as a promising technology for efficient rational use of available resources and sustained productivity in the long run. By saving inputs, reducing energy usage and greenhouse gases emissions, CA-based management practices are quite viable for bringing sustenance in agricultural crop production. The CA system can provide multiple ecosystem services such as provisioning, regulating and supporting services. The regulating services include improving carbon status, and physical, chemical and biological properties of soil, which further lead to provisioning services in terms of sustained crop and water productivity. Increased soil carbon sequestration improves supporting services, namely, soil aggregation that increases available soil moisture and can be helpful for better plant growth and development. It also improves soil biodiversity both above-and below-ground. Here we focus on the potential ecosystem service benefits accrued from CA. Conservation agriculture in the long run can be a strategy for sustainable crop intensification and a climate resilient crop management system.